Social networking at the University - student research patterns and online activities - Banek Zorica, Mihaela (Array, 2010)
Paper discusses the results of survey conducted in January 2010 with graduate students of Faculty of Humanities and Social Sciences, University of Zagreb. This research aims to shed some light on students' information universes, their perception of the library, use of online services, and new approaches to the educational information space, mainly based on social networking and its tools, influencing the change in traditional models of communication and knowledge transfer